Katara’s Authenticity in Avatar: The Last Airbender - Klarissa Yohanna; Pratiwi Retnaningdyah (Tell : Teaching of English Language and Literature Journal, 2022)
Authenticity is an important quality every individual should have as it reflects self-understanding and healthy functioning. However, due to the societal norms, such as gender stereotypes, the idea of being authentic has become a challenge. Oftentimes, when it comes to gender stereotypes, women get the short end of the stick—underestimated, ignored, and sexualized. The uprising feminism movement indeed makes a great impact of how women are viewed, but the media is still lacking of authentic representation of female character who isn’t trying to fit into a certain role. Avatar: The Last Airbender is able to provide that through Katara character despite it being a children’s TV series. Using the theory by Kernis and Goldman, this paper explores the four multicomponents of authenticity—awareness, unbiased processing, behaviour, relational orientation—which are all possessed by Katara; furthermore, proving her authenticity. This paper argues that Katara is able to maintain her authenticity by acting in accordance with her internal values, particularly in terms of equality and justice. In so doing, she manages to fight sexism and empower the oppressed.